2020
DOI: 10.5664/jcsm.8188
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the modified Mallampati grade and Friedman tongue position in the assessment of obstructive sleep apnea

Abstract: Study Objectives: The modified Mallampati (MM) grade and Friedman tongue position (FTP) are commonly used scales that assess the oropharynx during evaluation for obstructive sleep apnea (OSA). Though used by many practitioners, there is controversy in the literature regarding their practical utility. The goal of this review will be to review the history of how the MM and FTP were developed, to discuss current evidence for their usefulness in the workup of OSA, and to provide future direction to better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
19
0
6
Order By: Relevance
“…14 Both have proven useful in assessing those with OSA. 15 However, the FTP better reflects OSA severity than the MMC, 16 and it is considered a classic indicator of OSA, while effectively informing surgical selection. 17 Although many studies have identified a strong association between an increased OSA incidence and severity and an increased score in the MMP/FTP classifications, [9][10][11]18 the clinical features correlated with FTP grades remain diverse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Both have proven useful in assessing those with OSA. 15 However, the FTP better reflects OSA severity than the MMC, 16 and it is considered a classic indicator of OSA, while effectively informing surgical selection. 17 Although many studies have identified a strong association between an increased OSA incidence and severity and an increased score in the MMP/FTP classifications, [9][10][11]18 the clinical features correlated with FTP grades remain diverse.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Both have proven useful in assessing those with OSA. 15 However, the FTP better reflects OSA severity than the MMC, 16 and it is considered a classic indicator of OSA, while effectively informing surgical selection. 17 …”
Section: Introductionmentioning
confidence: 99%
“…The Epworth sleepiness scale (ESS) [ 26 ] was used to assess excessive daytime sleepiness; the Pittsburgh sleep quality index (PSQI) [ 27 ] was used to assess sleep quality and other potential sleep-related symptoms; the 7-item generalized anxiety disorder scale (GAD-7) [ 28 ] and the 9-item patient health questionnaire (PHQ-9) [ 29 ] were used to assess anxiety and depression symptoms. The Mallampati score was also obtained during the screening period for each participant as previously described [ 30 ]. Morning questionnaires, including self-reported sleep latency, total sleep time and wake periods after sleep onset, were used to evaluate subjective sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…12 A more recent review of modified Mallampati grading noted its variable utility predicting OSA presence and severity even in in-person research settings, with lack of examination technique standardization potentially contributing to this inconsistency. 13 Therefore, challenges in proper upper airway grading and questions about its applicability to OSA risk assessment have long existed independently of telemedicine. Intensified roll-out of this health care modality is undoubtedly, and appropriately, heightening awareness of diagnostic and predictive dilemmas that already exist.…”
mentioning
confidence: 99%
“…Suboptimal interrater reliability, whether assessed through telemedicine or in-person care, is not cause to eliminate a particular physical examination maneuver or to avoid the patient encounter modality (eg, telemedicine) in which it was performed. On the contrary, these findings should spur us to re-examine our evaluation techniques 13 while reassessing how to dovetail them with historical factors during OSA risk assessment. There is little doubt that telemedicine-particularly C2H and OOC CVT-can complicate this process further due to its inherent logistical complexities.…”
mentioning
confidence: 99%